CREATING AN ELECTRONIC EDUCATIONAL RESOURCE IN THE SUBJECT OF "COMPUTER MAINTENANCE" USING THE AUTO PLAY SOFTWARE TOOL - Xakimova Yoqutxon Toxirjon qizi (Western European Studies, 2024)
The article explains the process of creating an electronic educational resource of "Computer maintenance" for students of mathematics and informatics education in higher education institutions and the process of using the Auto Play program in its creation.
Keywords: Auto Play; electronic resource; computer support